Advanced ordered mesoporous carbon with fast Li-ion diffusion for lithium–selenium sulfide batteries in a carbonate-based electrolyte. (December 2020) - Kim, Wonhee; Lee, Jiyeon; Lee, Seungmin; Eom, KwangSup; Pak, Chanho; Kim, Hyeong-Jin
Abstract: Lithium-selenium sulfide (Li–SeS2 ) batteries are promising next-generation batteries due to their high energy density (1124 mAh g −1 and 3372 mAh cm −3 ). In a carbonate-based electrolyte, Li–SeS2 batteries show excellent cycle life but low discharge voltage. This low discharge voltage is affected by the SeS2 content in the composite. To increase the energy density, both the discharge voltage and SeS2 content should be elevated simultaneously. Herein, various structures of ordered mesoporous carbons (OMCs) are investigated to overcome the low discharge voltage while containing a high SeS2 content. By tuning the OMC structure with a large pore volume and effective morphology, Li-ion diffusion is improved, thus leading to decreased ohmic resistance and charge-transfer resistance. Even at a high SeS2 content of 75 wt.%, a platelet-type OMC (POMC2.0) with a pore volume of 2.0 cm 3 g −1 enables operation at 2.0 V in a carbonate-based electrolyte. The Li–SeS2 batteries show excellent cycle performance with an average capacity of 552 mAh g −1 for 1600 cycles in a carbonate-based electrolyte. Graphical abstract: Image 1 Highlights: Various structures of ordered mesoporous carbons (OMCs) are synthesized. The advanced OMC structure has an effective morphology and high pore volume. POMC2.0 and ROMC2.2 with a high content of SeS2 (75 wt%) discharged at 2.0 V. The carbon structure affects the fast Li-ion diffusivity, leading to a low IR drop and Rct . The advanced OMC shows a stable cycle life of 552 mAh g −1 for 1600 cycles.